Use of Nonsteroidal Anti-Inflammatory Drugs and Risk of Chronic Kidney Disease in Subjects With Hypertension: Nationwide Longitudinal Cohort Study - Hsu, Chih-Cheng; Wang, Hongjian; Hsu, Yueh-Han; Chuang, Shao-Yuan; Huang, Ya-Wen; Chang, Yu-Kang; Liu, Jia-Sin; Hsiung, Chao A.; Tsai, Hui-Ju (Hypertension (Dallas, Tex. 1979), 2015)
Limited studies have examined the effects of nonsteroidal anti-inflammatory drug (NSAID) use on the risk of chronic kidney disease (CKD), especially in subjects with hypertension. Using National Health Insurance claims data in Taiwan, we conducted a propensity score–matched cohort study to investigate the relationship between NSAID use and CKD in subjects with hypertension. A total of 31976 subjects were included in this studysubjects not taking any NSAIDs in 2007 (n=10782); subjects taking NSAIDs for 1 to 89 days in 2007 (n=10605); and subjects taking NSAIDs for ≥90 days in 2007 (n=10589). We performed multivariable proportional hazard models to determine the relationship between NSAID use and CKD. The results showed that NSAID use was associated with a 1.18-fold increased risk of CKD in subjects taking NSAIDs for 1 to 89 days; and a 1.32-fold increased risk of CKD in hypertension subjects taking NSAIDs for ≥90 days, compared with subjects not taking any NSAIDs, after controlling for the confounding factors. In subgroup analyses, subjects taking NSAIDs for ≥90 days, >1 defined daily dose per day or taking NSAIDs >15 cumulative defined daily doses had a greater risk of CKD than subjects not taking any NSAID, but not for congestive heart failure, stroke, cancer, osteoarthritis, or rheumatoid arthritis. These results provide supportive evidence that NSAID use is associated with increased risk of CKD in subjects with hypertension. It is important to closely monitor the effects of NSAID use, particularly in patients with hypertension, a susceptible population for CKD.